2008
DOI: 10.1111/j.1444-2906.2008.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Separation and characterization of connective tissue cells expressing 43-kDa zinc-binding protein from common carp

Abstract: To separate the connective tissue cells expressing the 43-kDa zinc-binding protein from the common carp, mucosa of the digestive tract of the fish was removed by scraping with a glass slide, and the de-mucosa tissue was digested with a collagenase type IV solution. The cells collected from the collagenase-treated suspension were rather homogeneous, and more than 90% of the cells were round with a diameter of approximately 6 mm. Significant quantities of the 43 kDa zinc-binding protein were shown to be present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…An indirect immunohistochemical staining experiment using antibodies against the 43-kDa zinc-binding protein indicated that in the common carp digestive tract, the protein is mainly located in the connective tissue of the lamina propria and submucosal layer [16]. Connective tissue cells, likely fibroblasts, contain this protein, which loosely binds zinc on its outward-facing side [17]. In fibroblasts, the 43-kDa protein had a single type of binding site specific for zinc.…”
Section: Digestive Tract Tissue As a Zinc Storage Site In Common Carpmentioning
confidence: 99%
See 1 more Smart Citation
“…An indirect immunohistochemical staining experiment using antibodies against the 43-kDa zinc-binding protein indicated that in the common carp digestive tract, the protein is mainly located in the connective tissue of the lamina propria and submucosal layer [16]. Connective tissue cells, likely fibroblasts, contain this protein, which loosely binds zinc on its outward-facing side [17]. In fibroblasts, the 43-kDa protein had a single type of binding site specific for zinc.…”
Section: Digestive Tract Tissue As a Zinc Storage Site In Common Carpmentioning
confidence: 99%
“…Negative controls were performed by incubating cells with normal rabbit serum instead of primary antibody. Blood cells were observed using fluorescent microscopy [17].…”
Section: Stainingmentioning
confidence: 99%